Job insecurity and emotional disturbance of Polish employees during pandemic COVID-19 - Teresa Chirkowska-Smolak; Mykola Chumak (Nofer Institute of Occupational Medicine, 2021)
Background The pandemic, as an event that is new and dangerous to the health and life of the population, has put employees at risk of losing their job and experiencing deteriorating working and employment conditions. In this situation, authors were particularly concerned with the extent to which job insecurity (both quantitative and qualitative) contributed to the deterioration of workers' well-being. Material and Methods The study was carried out on 382 Polish employees in April and May 2020. The following research tools were used: the Job Insecurity in Pandemic Scale by Chirkowska-Smolak and Czumak and the Depression , Anxiety , Stress Scale (DASS-21) by Levibond and Levibond. Results The quantitative and qualitative job insecurity were significant predictors of depression and stress, but they did not explain anxiety symptoms. The scope of the explained variance of these negative emotional states by concerns related to work and employment was not large (from 11% to 17.6%). The moderating role of perceived employability was confirmed only in the case of the relationship between qualitative job insecurity and depression, as well as quantitative job insecurity and stress. However, the increase in the explained variance was very small. Conclusions Uncertainty related to the maintenance of employment and concerns about the deterioration of working conditions due to the COVID-19 pandemic had an impact on emotional disturbances of employees, but they only explained some of the variance of depression and stress and did not affect the perceived level of anxiety. The smaller role of economic stress in the emergence of negative emotional states could be associated with the occurrence of much more serious threats to the health and life of the population in this period. The very low level of unemployment in Poland, which remained at a similar level throughout the pandemic despite the catastrophic forecasts of economists, could also have played an important role. Med Pr. 2021;72(6):645-52